(untitled) (Web of Teachers: Inderscience Research, 2024)
The article is devoted to the study of the effectiveness of the drug etifoxine (strezam) in complex premedication in gynecological patients against the background of pathological menopausal syndrome with anxiety-depressive disorder. The use of stresam in premedication of gynecological patients has shown that the level of medical and social rehabilitation increases, and the length of stay of patients in the hospital is reduced.